2016
DOI: 10.1111/and.12561
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of quercetin against arsenic-induced testicular damage in rats

Abstract: This study investigated the effect of quercetin on changes in testes due to arsenic exposure. Twenty-seven male rats were divided into three groups: control (10 ml kg day saline), arsenic (10 mg kg day sodium arsenite) and arsenic + quercetin (arsenic + 50 mg kg day quercetin). The rats were sacrificed at the end of 15-day experiment. There was no difference between control group and arsenic group in body weight gain, testicular weight and serum total testosterone level. Quercetin treatment did not cause a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…The present study investigated the protective effect of administration of C. afer leaves' methanol extract (at 100 and 200 mg/kg body weight) in the model of cadmium‐induced toxicity rats. Cadmium is considered as a reproductive toxicant (Baltaci et al, ; Farombi et al, ). Environmental exposure to cadmium was associated with poor semen quality and male infertility (Benoff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study investigated the protective effect of administration of C. afer leaves' methanol extract (at 100 and 200 mg/kg body weight) in the model of cadmium‐induced toxicity rats. Cadmium is considered as a reproductive toxicant (Baltaci et al, ; Farombi et al, ). Environmental exposure to cadmium was associated with poor semen quality and male infertility (Benoff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, quercetin (50 mg kg −1 day −1 , for 15 days) significantly increased testosterone level in arsenic-induced reproductive damage in rats [47]. In addition, quercetin at 90 mg −1 kg −1 day −1 for 15 days was found to enhance testosterone production in male rats with di-(2-ethylhexyl) phthalate-induced reproductive toxicity [48].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Recently, it has been shown that quercetin at 20 mg −1 kg −1 of body weight for 28 days is able to attenuate testosterone depletion induced by cadmium chloride in male Wistar rats [51]. Such protective effects may be attributable to the antioxidant activity of quercetin as it was found to increase the activity of testicular antioxidants (superoxide dismutase, glutathione reductase, and catalase) and significantly reduce the level of malondialdehyde in testicular tissue [47,50,52].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…It is suggested that arsenic‐induced male reproductive toxicity at least in part occurs via excess generation of reactive oxygen species (ROS), inhibition of testosterone synthesis, and also altering protein functions (via binding thiol groups) . Since arsenic intoxication has been linked to oxidative stress, several studies highlighted the significance of antioxidants such as N ‐acetyl cysteine, melatonin, and quercetin against the arsenic‐induced male reproductive toxicity in experimental animals. The present study is focused on α‐lipoic acid (LA: 1,2, dithiolane‐3‐pentanoic acid), which is classically known as “universal antioxidant.”…”
Section: Introductionmentioning
confidence: 99%